Anxiety, depression and eating behavior of university students during and after the COVID-19 pandemic: What is known? (Research, Society and Development, 2025)
Anxiety disorders and depression affect many individuals around the world. Anxiety is characterized by an anticipated sense of discomfort in the face of an adverse situation, while depression is described as a feeling of constant sadness. These two factors influence eating behavior, as preferences for hyperpalatable foods can emerge. With the COVID-19 pandemic and the rise of social isolation and remote learning, feelings of uncertainty about the future have also emerged among university students, increasing cases of anxiety and depression. Even after the relaxation of isolation measures, behaviors stemming from the pandemic persist. The present study aimed to evaluate anxiety, depression and eating behavior of university students during and after the COVID-19 pandemic. To this end, an integrative literature review was conducted in the PubMed, Capes Periodicals, and Virtual Health Library databases, using the descriptors: Anxiety, Depression, Feeding Behavior, Students, and COVID-19, between 2020 and 2025. Based on the analysis of the articles, it was observed that the COVID-19 pandemic impacted the mental health and eating behavior of university students. Studies have shown an increase in cases of anxiety and depression among higher education students. Regarding eating behavior, an increase in the consumption of healthy foods and a reduction in fast food consumption were observed, as well as greater health concerns in the face of the pandemic. It is noteworthy that few studies have evaluated mental health and eating behavior in the post-pandemic period.